The Effect of The Use of Different Types and Levels of Tapioca Flour on The Physical Quality of Rabbit Meatballs - Aris Sri Widati; Mustakim Mustakim; Eny Sri Widyastuti; Herly Evanuarini; Dedes Amertaningtyas; Mulia Winirsya Apriliyani (Faculty of Animal Science Universitas Brawijaya, 2022)
The purpose of this research was to determine the best type and level of tapioca flour in rabbit meatballs based on pH, WHC, cooking loss, and color. Rabbit meat and tapioca flour were used as research materials. The method used is a laboratory experiment using a completely randomized design with a factorial pattern. Factor A is the type of tapioca flour, namely dragon tapioca flour and special tapioca flour. Factor B is the level of use of tapioca flour, namely 25% and 50%. The pH value, WHC, cooking loss, and color used as the analyzed variable. Data analysis used Analysis of Variance and if there was a significant effect, it was continued with Duncan's Multiple Distance Test or DMRT. The results showed that the treatment using different types and levels of tapioca flour had a highly significant difference effect (P < 0.01) on WHC, cooking loss, L, a*, and b* and had no effect (P>0.05) on rabbit meatball pH. It can be concluded that tapioca special flour with level 25% gives the best results on characteristic of rabbit meatball.